2016
DOI: 10.1038/srep28456
|View full text |Cite
|
Sign up to set email alerts
|

Triggering comprehensive enhancement in oxygen evolution reaction by using newly created solvent

Abstract: Theoretical calculations indicate that the properties of confined liquid water, or liquid water at surfaces, are dramatically different from those of liquid bulk water. Here we present an experimentally innovative strategy on comprehensively efficient oxygen evolution reaction (OER) utilizing plasmon-induced activated water, creating from hot electron decay at resonantly illuminated Au nanoparticles (NPs). Compared to conventional deionized (DI) water, the created water owns intrinsically reduced hydrogen-bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…On the other hand, our group proposed an innovative method to create plasmon-activated water (PAW), which is prepared by treating deionized (DI) water with resonantly excited AuNPs [ 23 , 65 , 66 ]. Recently, the PAW-related papers, which are innovatively applicable in variously fields, are continuously published in our group [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Compared to DI water, the created additive-free PAW shows lower specific heat and boiling point [ 66 ], higher vapor pressure and osmosis [ 23 ], novel antioxidant and anti-inflammatory properties [ 23 , 67 ], and higher solubility and diffusion to solutes [ 23 , 65 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our group proposed an innovative method to create plasmon-activated water (PAW), which is prepared by treating deionized (DI) water with resonantly excited AuNPs [ 23 , 65 , 66 ]. Recently, the PAW-related papers, which are innovatively applicable in variously fields, are continuously published in our group [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Compared to DI water, the created additive-free PAW shows lower specific heat and boiling point [ 66 ], higher vapor pressure and osmosis [ 23 ], novel antioxidant and anti-inflammatory properties [ 23 , 67 ], and higher solubility and diffusion to solutes [ 23 , 65 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to DI water, the created additive-free PAW shows lower specific heat and boiling point [ 66 ], higher vapor pressure and osmosis [ 23 ], novel antioxidant and anti-inflammatory properties [ 23 , 67 ], and higher solubility and diffusion to solutes [ 23 , 65 , 67 ]. Based on these distinct properties, PAW can be served as source of green energy for improving the efficiencies of productions of hydrogen and oxygen via water splitting [ 65 , 69 , 72 ]. In green chemistry, PAW can be employed as a green reductant for production of AuNPs and AgNPs from their individual ions [ 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…As per the study on triggering comprehensive enhancement in oxygen evolution reactions (OERs) by using PAW, we reported that the created PAW has an advantage in OERs because the corresponding activation energy can be effectively reduced by itself. 31 Figure 6A shows the linear scan voltammograms (LSVs) of OERs performed in 0.1 N KCl based on as-prepared PAW, 10 day aged PAW-4-10, and DI water. Clearly, the recorded currents are higher for as-prepared PAW and PAW-4-10, compared to DI water.…”
Section: Resultsmentioning
confidence: 99%
“…So far, nineteen PAW-related papers have been published. Examples of this are its creation mechanism , and its innovative applications in green energies of evolution reactions of oxygen and hydrogen, medicine (lung cancer, hemodialysis, and chronic sleep deprivation), chemical reactions, and physical processes. However, the activity of the resulting metastable PAW decayed after its creation for a couple of days. ,, For expanding convenience in application of PAW, an innovative strategy on persisting PAW’s distinct activities is proposed by utilizing quickly freezing and melting methods in this work. The distinct properties and anti-oxidative activity, as compared to bulk water, of as-prepared and aged PAW are compared to each other in detail.…”
Section: Introductionmentioning
confidence: 99%
“… 17,33 Besides, PAW can also retain its properties in alkaline solution. 34 This means that PAW is stable in neutral, acidic and alkaline environments such as the stomach, liver and gut, respectively. This is just the case in our current study.…”
Section: Discussionmentioning
confidence: 99%